[Poster] Identifying Maintenance, Repair and Overhaul Events based on ADS-B Data - Arts, Emy; Meyer, Hendrik; Raddatz, Florian; Wende, Gerko (Journal of Open Aviation Science, 2023)
Maintenance, Repair and Overhaul (MRO) plays a big role in aviation schedules and operational costs. In this work service difficulty reports are combined with aircraft ADS-B data to identify MRO activity based on an aircraft's layover information. The ``Inspection/Maintenance'' stage of operation and date of service difficulty reports allow to label layovers from ADS-B with the presence of MRO activity. Using a support vector machine this work classifies layovers based on their duration and time of day, achieving an 86% overall accuracy and 78% balanced accuracy. These results reflect the difficulty of working with this sparse and incomplete dataset, however, they allow us to study MRO schedules. The combination of these data sources offers new opportunities to find relations between aircraft trajectory information and MRO, which will be further investigated in future work.